2017
DOI: 10.1016/j.watres.2016.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the effects of past flood events and perceived and estimated flood risks on individuals' voluntary flood insurance purchase behavior

Abstract: Over the past several decades, the economic damage from flooding in the coastal areas has greatly increased due to rapid coastal development coupled with possible climate change impacts. One effective way to mitigate excessive economic losses from flooding is to purchase flood insurance. Only a minority of coastal residents however have taken this preventive measure. Using original survey data for all coastal counties of the United States Gulf Coast merged with contextual data, this study examines the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 48 publications
2
49
0
1
Order By: Relevance
“…To investigate how flood insurance purchase behavior influences individuals' mitigation policy support among the US Gulf Coast residents, we use a comprehensive climate change survey for all coastal counties in the Gulf Coast in 2012 (SM 1). In addition to flood insurance purchase behaviors, the survey includes various questions related to socio-demographic characteristics, perceptions of local climate change, and perceptions of flood-related hazards that may affect mitigation behavior/intention [28][29][30][31][32]. We construct an interconnected Bayesian Network (BN) model to study how these variables jointly affect the support for flood mitigation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate how flood insurance purchase behavior influences individuals' mitigation policy support among the US Gulf Coast residents, we use a comprehensive climate change survey for all coastal counties in the Gulf Coast in 2012 (SM 1). In addition to flood insurance purchase behaviors, the survey includes various questions related to socio-demographic characteristics, perceptions of local climate change, and perceptions of flood-related hazards that may affect mitigation behavior/intention [28][29][30][31][32]. We construct an interconnected Bayesian Network (BN) model to study how these variables jointly affect the support for flood mitigation.…”
Section: Methodsmentioning
confidence: 99%
“…We also consider the geographic context represented by the percentage of land area of the Special Flood Hazard Area (SFHA) 6 per county. The SFHA is designated by the Federal Emergency Management Agency's (FEMA's) flood map, and it is found to be positively related to perceptions of changing flood amount [32] and voluntary flood insurance purchase behavior [31]. Tenure-the length of residence in the coastal region -indicates exposure to coastal hazards and experience with hazards.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of hurricanes, Trumbo et al [43] found that during the quiescent three-year period after the 2005 hurricane season, when Katrina and Rita struck, hurricane risk perception declined and optimism bias (believing others are more likely to suffer harm than oneself) increased. Additional evidence of a recency effect on preparation decisions can be found in voluntary flood insurance purchases, which were predicted in one study by peak storm surge heights during the most recent hurricane [44]. The availability heuristic can also make it difficult for people to imagine that future hurricanes may behave differently from past ones (Kates [45] referred to the participants of his study as "prisoners of experience").…”
Section: Prior Storm Experiencementioning
confidence: 98%
“…Recent empirical research has found that peoples' motivation of voluntary risk mitigation and adaptation is low unless actual risk can be perceived (Botzen et al 2009;Kunreuther and Slovic 1978;Kunreuther and Weber 2014;Lindell and Hwang 2008;Shao et al 2017b;Shao et al 2017c). Risk perceptions can influence peoples' willingness to respond to, recover from, and adapt to hurricanes and other extreme events (Hertwig et al 2004;Kasperson et al 1988;Loewenstein et al 2001).…”
Section: Introductionmentioning
confidence: 99%